Differential efficacy of the TSPO ligands etifoxine and XBD-173 in two rodent models of Multiple Sclerosis. (September 2016) - Ravikumar, Brinda; Crawford, Dan; Dellovade, Tammy; Savinainen, Anneli; Graham, Danielle; Liere, Philippe; Oudinet, Jean-Paul; Webb, Mike; Hering, Heike
Abstract: Neurosteroids such as progesterone and allopregnanolone have been shown to exert neuroprotective effects under a variety of pathological or insult conditions, and there is evidence that the neurosteroid system is perturbed in Multiple Sclerosis (MS) patients. Neurosteroids are synthesized in the central nervous system (CNS) through a series of metabolic transformations, beginning with a rate-limiting step of cholesterol transport through the outer mitochondrial membrane via the transporter translocator protein (TSPO). We examined the effects of etifoxine and XBD-173, two different brain penetrant TSPO agonists, for their ability to ameliorate clinical signs in two different experimental autoimmune encephalitis (EAE) models. Etifoxine, as previously reported, was efficacious in EAE, while XBD-173 was not. Surprisingly, XBD-173, but not etifoxine elevated relevant neurosteroids in brain of female rats and differed in its ability to exert anti-inflammatory and direct neuroprotective effects in vitro as compared to etifoxine. We conclude that the neurosteroid elevations produced in brain by XBD-173 are not sufficient to ameliorate EAE and suggest that etifoxine may have additional mechanisms of action that provide therapeutic benefit in this model system. Highlights: TSPO agonist etifoxine ameliorates disease course in EAE through both direct neuroprotection and anti-inflammatory activity. TSPO agonist XBD-173 fails to provide therapeutic benefit in EAE despite its ability to elevate neurosteroids in brain. Differential pharmacology of TSPO ligands determine their efficacy in EAE.